Du Pont Analysis System to Assess Financial Performance PT. Semen Indonesia (Persero) Tbk. Before and After Acquisition - NORA, SHELY (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This study aims to determine the financial performance of PT Semen IndonesiaTbk before and after the acquisition of Thang Long Cement, Vietnam. This study uses a model of du pont system consisting of the calculation of net profit margin, total asset turnover, return on investment, debt ratio, and return on equity. The object of this research is PT Semen Indonesia Tbk period 2010-2014. This research is quantitative descriptive with case study approach that describes the state of the financial performance of PT Semen Indonesia Tbk between before and after the acquisition.The results showed that the company's profit margin margin fluctuated and tended to decrease, but actually improved on the time of acquisition. TATO value of the company prior to the acquisition decreased, and now improved and stabilized after the acquisition. ROI is the constant company declined over the last five years. In terms of financing, the proportion of debt is the highest in the year of acquisition, and declined thereafter. ROE value of the company prior to the acquisition of decline, but it improved at the time of acquisition, then back downhill.Keywords: financial performance, acquisitions, system du pont